Socio-legal reflections on the Church-State separation - Cordero Rodríguez, Luis (2007)
As a professor he used to teach the excellency of the establishment clause in the American Constitution about the relationship betweenthe Churches and the American State. Precisely in the present article he presents this excellency, and studied the impossibility for the European and West Christian Countries, to copy this American way, because the History of the different Christian Countries are, by no doubt, very different, and cannot be compared with the History of USA and its different religion Confessions. Also the conception of Privacy is very different in those countries. In fact, nearly all of the different European Countries use the Public Right of the State in all events of Private life (School, Religion, Taxes, Welfare, etc), which is exactly the opposite way done by USA where Privacy is sacred; and Religion is in the field of privacy, therefore it is incompatible with Public Life, and any Church cannot be on welfare (or on US social Security